Optimalization of DNA isolation from oral epithelial mucous cell with smear method - Nasroen, Saskia L.; Maskoen, Ani Melani; Nurwiadh, Agus (Padjadjaran Journal of Dentistry, 2009)
Deoxyribonucleic acid (DNA) is a genetic material which is found in all living organisms. On the human cell or eukaryotes cell, the DNA is found in the nucleus cell and the mitochondria. The DNA arrangement on each cell in human body is the same, that is why, for the analysis meaning, DNA can be isolated from any cell in the body. The source of DNA to be analyzed usually coming from the blood sample by an injection method, such a way resulting in pain and bringing about constraint. Therefore, a study was carried out to look for an alternative of DNA isolation. The aim of this experimental study was to get an optimal DNA isolation method by using oral mucous smear method with a purpose to get a quick and easy DNA isolation. The investigation materials were in the form of samples which were taken from the oral epithelial mucous cells out of three different subjects. The epithelial cells were obtained by the oral mucous smear method which in a variation of two, four and six times of smear applications, respectively. The DNA was then isolated using buffer extraction method. The concentrations of DNA were measured by using ultraviolet spectrophotometer at 260 nm wavelength. The results of DNA isolation were analyzed by Polymerase Chain Reaction (PCR) technique. The optimal DNA isolation could be analyzed by PCR technique. The experimental results show that from three different subjects of study, DNA can be isolated optimally by oral mucous smear method with six times of smear applications.